Istanbul and water (Leuven)
x, 274 s.
Keywords: "Istanbul stands at a unique conjunction of an inland sea with a long maritime inlet, and a winding, turbulent maritime strait that links two seas and separates two continents. These topographical features have greatly facilitated maritime trade, for which the city has had an enormous harbor capacity. Istanbul's relationship with fresh water is also idiosyncratic: its dearth meant that fresh water for consumption had to be channeled, stored, and distributed with the help of long-distance aqueducts, open-air reservoirs and cisterns. The natural environment combined with the norms of local societies created a culture of water that has constituted an important part of Istanbul's identity. Various aspects of it are explored in this volume, the outcome of a symposium organized by Koç University's Research Center for Anatolian Civilizations. The eleven essays by leading scholars present recent research findings from the archaeological excavations at Yenikapi, examine the distribution and consumption of water in Byzantine times as well as the social impact of water in the Ottoman era, and offer reflections on the aesthetics of water." --